LOOSEPART BERBASIS PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KEMAMPUAN PRA MEMBACA ANAK USIA DINI - Badi’atus Solihah; Sarah Emmanuel Haryono; Siti Muntomimah (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
The pre-reading ability of children in Group B at TK Muslimat NU 1 Raudlatul Ulum is still relatively low; out of 17 children, 10 were unable to recognize the syllable cards ba, ca, and da (consonant-vowel). This study aimed to examine the effectiveness of implementing loosepart media based on Project Based Learning (PjBL) in improving children's pre-reading skills. The research employed a Classroom Action Research (CAR) approach with two cycles, each consisting of planning, implementation, observation, and reflection, involving 17 children as subjects. The instruments used included observation sheets and interview guides, analyzed qualitatively. The results showed a significant improvement in pre-reading ability; 95% of the children were able to recognize vowels, consonants, and spell consonant-vowel syllables correctly after the implementation of loosepart based on PjBL. These findings indicate that loosepart media based on PjBL is effective in supporting early literacy development, while also providing an innovative learning strategy that can be applied in kindergartens to enhance children's reading skills from an early age. Keywords:  early childhood; pre-reading; loose parts; Project Based Learning